Stokes posets and serpent nests - Chapoton, Frédéric (Discrete Mathematics and Theoretical Computer Science, 2016)
30 pages, 12 figures We study two different objects attached to an arbitrary quadrangulation of a regular polygon. The first one is a poset, closely related to the Stokes polytopes introduced by Baryshnikov. The second one is a set of some paths configurations inside the quadrangulation, satisfying some specific constraints. These objects provide a generalisation of the existing combinatorics of cluster algebras and nonnesting partitions of type A. On étudie deux objets attachés à une quadrangulation quelconque d'un polygone régulier. Le premier objet est un ensemble partiellement ordonné, fortement lié aux polytopes de Stokes introduits par Barysknikov. Le second est un ensemble de configurations de chemins dans la quadrangulation. Ces deux objets généralisent respectivement les aspects combinatoires des algèbres amassées et des partitions non-emboitées de type A.